Wideband High-Selectivity SIW Filtering Antenna with Controllable Radiation Nulls - Zhongbao Wang; Xinhong Liu; Hongmei Liu; Shaojun Fang (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2024)
Abstract A novel wideband high-selectivity substrate-integratedwaveguide (SIW) filtering antenna with controllable radiation nulls is proposed. This antenna is composed of a two-layered SIW resonator, two radiating slots on the top layer, and two coupling slots on the middle layer. A vertical SMA connector is located at the bottom and feeds two SIW cavities simultaneously. By adjusting the parameters of these slots, three radiation nulls will be achieved, and two radiation nulls can be easily controlled. For demonstration, one prototype of the filtering antenna is fabricated and measured. Measurement results show that the fractional bandwidth for |S11| < -10 dB is 8.9% (3.86-4.23 GHz), the gain is 6.08 dBi at center frequency 4.05 GHz, three radiation nulls are achieved at 3.7 GHz, 4.3 GHz, and 5.19 GHz, respectively. The out-of-band skirt selectivities of two sidebands are 150 and 332 dB/GHz, respectively.